ANALISIS DISTRIBUSI ZAKAT PADA BAZNAS DALAM PENCEGAHAN COVID-19 DITINJAU DARI MAQASHID SYARIAH - Jureid, Jureid (Faculty of Islamic Economics and Business, IAIN Lhokseumawe, 2021)
The outbreak of Covid-19 in Mandailing Natal has caused several problems in the economic, educational and social fields. The problems that occur certainly really need the role of Baznas in overcoming them. The purpose of this research is to find out how the distribution of zakat in the process of preventing Covid-19 in Mandailing Natal and to know the perspective of maqashid sharia on this distribution. The method used in this research is descriptive qualitative method in the review of maqashid sharia. The results of the research show that the zakat distribution mechanism is carried out by means of Baznas actively engaging the community to call for zakat, it is even recommended to the public to take part in paying without having to be visited by Baznas or other policies including the muzakki's own workplace. Zakat distributed is not only in the form of money or food but is adjusted to the needs of the people affected by Covid-19 and is distributed periodically and Baznas is actively monitoring and evaluating the program. Zakat as an Islamic fiscal instrument has helped ease the burden on people affected by Covid. Consumptive zakat or productive zakat can be a mental solution and make the mustahik prosperous. Zakat together with its derivatives has brought enormous benefits to affected communities or other mustahiks. Zakat can guarantee the continuity of life in various aspects including maintaining life, property, religion, reason and of course zakat is the main object of maqashid sharia towards a prosperous society